Modificaciones al Sistema General de Seguridad Social en Salud a la luz de una sentencia de la Corte Constitucional de Colombia: una propuesta (2009)
ABSTRACT: The ruling of the Constitutional Court T-760/2008 asked the government to match the health benefit plans, to facilitate the payment of bills, to consider health as a fundamental right and as such, ensure strict compliance with the respect, protection and health guarantee. This in view of the Social Security System (SSS) has not complied with the principles under which it was created and the results in this area are not expected. In the current economic crisis, social and policy in the country, it requires an analysis from the academy and to propose viable and sustained measures to guide the completion of sentence for the benefit of the fundamental right to health. This article examines the context, the key points of the decision and intends to achieve universal care, equating benefit plans, explore other funding sources, implement a care model based on renewable primary care, promote community participation and improving system control mechanisms. This is a proposal to enrich the debate